New Lightweight Identity Based Encryption Algorithm for Mobile Device: Preliminary Study - Norhidayah, Muhammad; Jasni, Mohamad Zain; Md Yazid, Mohd Saman (2012)
Recently the importance of mobile security coincides with the development of mobile computing. Mobile security has become the most important part of the mobile telecommunication, but mobile device has a limited processing capabilities, bandwidth is limited , high latency networks, storage capabilities are limited, lack of computing power to support strong encryption are constrained in using traditional encryption scheme such as RSA. Therefore for this study we try to create a new lightweight algorithm for mobile device, we want to implement identity based encryption with new feature, suitable for mobile device specification. Mobile information security should be enhanced to new scheme that more simple and use the small key size, also high security level. The main problem in traditional cryptosystem is a public key in determining validity, but this problem can be solved by identity based cryptography, where the public key can be obtained from users of public information known users. One method called elliptic curve will be implemented in IBE. Elliptic curve method has shorter key size, smaller signature length, fast operations and high security working. Thus, it is suitable for mobile devices, it uses 160 bits key and provides the same security as RSA 1024 bits key.Some benefits are expected from this study to improve the encryption algorithm for mobile security.